Science, colonialism, and indigenous peoples : the cultural politics of law and knowledge / Laurelyn Whitt. - Whitt, Laurelyn (Cambridge University Press, 2009)
At the intersection of indigenous studies, science studies, and legal studies lies a tense web of political issues of vital concern for the survival of indigenous nations. Numerous historians of science have documented the vital role of late-eighteenth- and nineteenth-century science as a part of statecraft, a means of extending empire. This book follows imperialism into the present, demonstrating how pursuit of knowledge of the natural world impacts, and is impacted by, indigenous peoples rather than nation-states. In extractive biocolonialism, the valued genetic resources, and associated agricultural and medicinal knowledge, of indigenous peoples are sought, legally converted into private intellectual property, transformed into commodities, and then placed for sale in genetic marketplaces. Science, Colonialism, and Indigenous Peoples critically examines these developments, demonstrating how contemporary relations between indigenous and Western knowledge systems continue to be shaped by the dynamics of power, the politics of property, and the apologetics of law.